Bibliometric Analysis On Research Study Of Pomegranate: A Review Towards New Findings) - Md Ariffin, Mohd Farhan (Program Studi Ilmu Perpustakaan UIN Alauddin, 2015)
Abstrak : Delima merupakan buah yang mengandung banyak kekayaan anti oksidan dan juga dapat digunakan sebagai alternatif dan bahan obat-obatan alami. Dari sudut pandang ilmu kesehatan pada masa lalu, delima termasuk dalam buah-buahan yang baik untuk kesehatan karena manfaatnya yang dapat mengobati beberapa jenis penyakit. Penelitian ini membahas tentang tren pada publikasi-publikasi mengenai delima. Penelitian ini difokuskan pada analisis konten, khususnya pada publikasi-publikasi penting tentang delima. Penelitian ini menunjukkan bahwa 85,5 persen penelitian-penelitian yang membahas tentang delima banyak terbit dalam bentuk jurnal artikel. Metode penelitan yang banyak digunakan pada penelitian-penelitian tersebut ialah analisis ilmiah (penelitian laboratori). Kajian mengenai aspek keilmuan dibagi menjadi tujuh bagian di antaranya diskusi ilmiah tentang delima yaitu farmasi, ilmu makanan, botani, biomedis, biokimia dan mikrobiologi. Hanya satu kajian yang fokus pada analisis keislaman yaitu pada sektor Pendidikan Islam. Bidang lainnya mengenai Lingkungan Pendidikan (Tumbuh-tumbuhan) juga terdapat pada penelitian ini yaitu dimaksudkan untuk mengumpulkan data dan menemukan hasil tentang tumbuh-tumbahan delima.Kata Kunci : Bibliometrik, Tren penelitian, Delima, Produk Malaysia Abstract : Pomegranates are an antioxidant-rich superfood with alternative and natural medicine resources for the natural health community. From the perspective of ancient medical practice, pomegranate is in a highest ranking of healthy fruits because of its diverse beneficial in curing diseases. Trend research publications pomegranates were studied. The study focused on content analysis, especially in the field of primary research on pomegranate. Referring to the results of literature review on pomegranate, researchers found that the majority of previous research on pomegranate dominated by journal articles by 85.5 percent. Research on the method of analysis conducted in the previous studies found that most studies on pomegranate done on a scientific analysis (laboratory studies). Studies on aspects of science has been divided into seven areas. Focus areas include scientific discussion of pomegranate is pharmaceutical, Food Science, Botany, Bio-Medical, Bio-Chemistry and Microbiology. Only one field of study that focuses on the analysis of Islamic view focusing on Islamic Education. Additional fields of Environmental Education (Flora) are also included by researchers to collect data and find a results on plants that contain pomegranate. Comparative evaluation of research found that a total of 188 kinds of studies involves the study of the scientific aspects compared to only 11 studies based on Islam (Islamic Education) and 10 studies based on environmental education. Thus, the efforts of researchers from Universiti Malaya through grants TRGS (TR001A-2014) entitled Safe and Health Uses of Fruits and Herbs Mentioned in Al-Quran and Ahadith: An Analysis of ethnomedicinal Importance in Islamic Products in Malaysia are very significant in the development of science. Advanced new study of henna is expected to produce benefits to Malaysia as a whole. Key Words: Bibliometrics, Research trend, Pomegranates, Malaysian product.